Code of ethics and code of practice: Two relevant documents for an effective and secure operation of tissue establishments - Pedraza, Jorge Morales (Archives of Surgery and Clinical Research, 2022)
Tissue banking is an interdisciplinary medical practice more reliant than others in specialized fields and applying knowledge from other branches of science, particularly nuclear sciences. A further difference from other medical disciplines is the urgent necessity to include laws, norms, standards and statutory regulations, which differ in their juridical binding force. Adopting a code of ethics and a code of practice is one of the main tasks to be conducted by a tissue establishment after its founding. The aim is to include in these codes the main ethical principles associated with the different laws, norms, standards, and statutory regulations in force in each country in the field of tissue banking.